2011
DOI: 10.1073/pnas.1109263108
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution microscopy reveals that mammalian mitochondrial nucleoids have a uniform size and frequently contain a single copy of mtDNA

Abstract: Mammalian mtDNA is packaged in DNA-protein complexes denoted mitochondrial nucleoids. The organization of the nucleoid is a very fundamental question in mitochondrial biology and will determine tissue segregation and transmission of mtDNA. We have used a combination of stimulated emission depletion microscopy, enabling a resolution well below the diffraction barrier, and molecular biology to study nucleoids in a panel of mammalian tissue culture cells. We report that the nucleoids labeled with antibodies again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
430
4
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 481 publications
(482 citation statements)
references
References 43 publications
30
430
4
4
Order By: Relevance
“…Mitochondrial transcription factor A (TFAM) is an appropriate marker protein because it is not only a mitochondrial transcription factor, but also a packaging factor of mtDNA. It has been shown on several occasions, both for the endogenous protein and overexpressed tagged variants that it constitutively labels all mtDNA molecules [37,65,66]. Indeed, here also the distribution pattern of TFAM (figure 3b) resembles that of mtDNA (figure 3a).…”
Section: The Measurement Of Mitochondrial Dynamics and Its Applicatiomentioning
confidence: 56%
See 2 more Smart Citations
“…Mitochondrial transcription factor A (TFAM) is an appropriate marker protein because it is not only a mitochondrial transcription factor, but also a packaging factor of mtDNA. It has been shown on several occasions, both for the endogenous protein and overexpressed tagged variants that it constitutively labels all mtDNA molecules [37,65,66]. Indeed, here also the distribution pattern of TFAM (figure 3b) resembles that of mtDNA (figure 3a).…”
Section: The Measurement Of Mitochondrial Dynamics and Its Applicatiomentioning
confidence: 56%
“…The size of mtDNA nucleoids roughly ranges from 50 to 300 nm based on EM and super-resolution microscopy [37,65]. This implies that in mitochondria with a regular arrangement of cristae discs with a mean distance of 53 nm, such as observed in HeLa cells [38], most nucleoids would not fit.…”
Section: The Measurement Of Mitochondrial Dynamics and Its Applicatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Current estimates from mammalian cell lines and mouse tissues indicate that TFAM is present at 1 copy per 15-20bp of mtDNA and it is thus likely to fully coat mtDNA 10,14 (Fig. 1).…”
mentioning
confidence: 99%
“…1). Super-resolution microscopy has revealed that the apparent mean size of nucleoids is ~100 nm in mammals 14 . By combining imaging and quantitative molecular approaches, it has been demonstrated that most nucleoids in human fibroblasts contain one single copy of mtDNA 14 .…”
mentioning
confidence: 99%